Synthesis and Electrical Properties of Water-Dispersible Polyaniline with a Polymer Template - Ugraskan, Volkan; Yazici, Ozlem; Karaman, Ferdane (SPRINGER, 2020)
Polyaniline (PANI) was synthesized using ammonium persulfate with different amounts of poly(4-sulfonic acid diphenyl aniline) (PSDA) as a template in order to obtain water-dispersible eco-friendly PANI:PSDA composites with enhanced thermoelectric properties. The synthesized composites were characterized by UV-Vis spectroscopy, FT-IR spectroscopy and scanning transmission electron microscopy. The particle sizes and zeta potentials of the PANI:PSDA dispersions were also measured. The electrical conductivity and Seebeck coefficient of PANI increased from 0.39 S m(-1) to 3.2 S m(-1) and from 21 mu V K-1 to 207 mu V K-1, respectively. The highest power factor was found in the 40% PSDA composition as 0.09 mu W m(-1) K-2, which is 500 times that of pristine PANI.
Keywords: Polyaniline; poly(4-sulfonic acid diphenyl aniline); electrical conductivity; water dispersibility; thermoelectric properties; POLYSTYRENE SULFONATE; CONDUCTING POLYMER; DOPED POLYANILINE; COMPOSITES; ANILINE; ACID; POLYELECTROLYTE; NANOPARTICLES; COPOLYMER; Engineering; Materials Science; Physics